Structure and assembly - Hesketh, John E.; Pryme, Ian F. (JAI Press, 1995)
This volume of the treatise deals with structural aspects of the cytoskeleton: the characteristics of the filaments and their components; the organization of the genes; motor proteins; interactions with membranes.